2007
DOI: 10.1016/j.bbalip.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of chylomicron remnant-like particles inhibits their uptake by THP-1 macrophages by apolipoprotein E-dependent processes

Abstract: The influence of the oxidative state of chylomicron remnants (CMR) on the mechanisms of their uptake and induction of lipid accumulation by macrophages derived from the human monocyte cell line, THP-1, during foam cell formation was investigated using chylomicron-remnant-like particles (CRLPs) at 3 different levels of oxidation. The oxidative state of CRLPs was varied by exposure to CuSO4 (oxCRLPs) or incorporation of the antioxidant, probucol (pCRLPs) into the particles. oxCRLPs caused significantly less accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
2
18
0
4
Order By: Relevance
“…4(a)). These findings are in agreement with those of previous work demonstrating a decreased mRNA expression of LDLR after the incubation of THP-1 macrophages with CM remnants ( 14 , 34 ) . It is known that the expression of this receptor is inhibited by the intracellular accumulation of cholesterol due to lipoprotein uptake ( 34 , 35 ) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…4(a)). These findings are in agreement with those of previous work demonstrating a decreased mRNA expression of LDLR after the incubation of THP-1 macrophages with CM remnants ( 14 , 34 ) . It is known that the expression of this receptor is inhibited by the intracellular accumulation of cholesterol due to lipoprotein uptake ( 34 , 35 ) .…”
Section: Discussionsupporting
confidence: 93%
“…This result, together with the visualisation of the lipid content with Oil Red O staining, suggests that postprandial TRL induce the formation of foam cells in THP-1 cell populations mainly by TAG, rather than cholesterol, accumulation. Although there is a great deal of evidence from studies carried out both in vivo and with THP-1 macrophages to indicate that foam cell formation induced by native or modified LDL is caused by the accumulation of CE ( 31 ) , our findings are consistent with those of extensive previous work showing that CM remnants cause excessive TAG accumulation in human monocyte-derived macrophages as well as in the mouse macrophage cell line J774 and THP-1 macrophages ( 6 , 14 , 17 , 32 , 33 ) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pathways mediating macrophage uptake of chylomicron remnants are apolipoproteinE (apoE)-dependent receptor-mediated processes involving the LDL receptor and the LDL receptor-related protein (LRP) [911]. However, several studies have found evidence that chylomicron remnant uptake pathways in these cells may be independent of the LDL receptor [6, 12] and apoE production [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main uptake and internalisation being through the LDL receptor related protein (LRP) and the LDL receptor [97]. GLP-1-like agonists are now being widely used in the treatment of diabetes and have a beneficial effect on glycaemia and also lipidaemia [98]. Xiao et al 2011 [99] have recently shown in healthy men that glucagon acutely regulates hepatic but not intestinal lipoprotein www.intechopen.com metabolism both by decreasing lipoprotein particle production and inhibiting particle clearance.…”
Section: Chylomicron and Atherosclerosismentioning
confidence: 99%